1998
DOI: 10.7601/mez.49.195
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of indoor searches with whole house demolition collections of the vectors of Chagas disease and their indoor distribution

Abstract: The number of Triatoma dimidiata found per rnan-hour of collection in each of the three mud-walled houses were 4, 1 and 37, In the third house 8 of T nitida were also collected.When the walls of these houses were dismantled, an additional 1 14, !41 and 307 of Tl dimidiata were cellected along with 34 of T nitida in the third house, In the palm-thatch roofed huts only Rhodnius Protixus were collected. The numbers per man-hour collected were 1 1, 27 and 26. When the roofs were dismantled and searched 75, 449 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 6 publications
0
34
0
Order By: Relevance
“…In a previous study (Monroy et al 1998b) we reported the case of one house where T. dimidiata and T. nitida were found together. In this house, T. dimidiata bugs were nine times more abundant and mainly positioned close to beds and chicken nests, while the specimens of T. nitida were dispersed throughout the house, probably compelled to disperse from suitable sites because of the competition with T. dimidiata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study (Monroy et al 1998b) we reported the case of one house where T. dimidiata and T. nitida were found together. In this house, T. dimidiata bugs were nine times more abundant and mainly positioned close to beds and chicken nests, while the specimens of T. nitida were dispersed throughout the house, probably compelled to disperse from suitable sites because of the competition with T. dimidiata.…”
Section: Discussionmentioning
confidence: 99%
“…Following Chagas control programs in Guatemala it is expected a diminution of the intradomestic presence of other triatomines (T. dimidiata, R. prolixus), the possibility exists in some areas that T. nitida could invade and colonize the empty microhabitats, based on our previous observation of competition with T. dimidiata (Monroy et al 1998b). We recommend on-going vigilance, especially in the department of Quiche, where the intradomestic colonization of T. dimidiata is not very high and more abundant in the peridomicile; also, the entomological surveys by the Ministry of Health in this department are showing that T. nitida is very common inside and outside the houses (Mr Guillermo Hernández, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Monroy and others compared the number of T. dimidiata found by the man-hour search method with that found after demolishing an entire house and showed that only 7.0% of the total bugs present could be found by the man-hour method. 24 This manual searching technique involves technical bias owing to inspectors' motivation and skill. It is possible that in our study, those bug inspectors who performed the first entomological evaluation had improved their bug searching skills by the second evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Bedrooms and sleeping areas were prioritized for spraying because T. dimidiata bugs are often found around beds. 24 Kitchens were not sprayed, to avoid contamination of stored food or water with insecticide. In particular, larger amounts of insecticide were deposited within cracks in walls, if present, for improved effectiveness against T. dimidiata hidden inside the cracks.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, a previous study in Guatemala reported that the method detected only 7% (= 42 of 604) of the total number of T. dimidiata bugs collected through demolition of mud walls. 22 Needless to say, counting the number of the bugs through demolition of mud walls provides the most accurate infestation rate. Yet, it is absolutely unrealistic to demolish mud walls of every target housing structure inhabitants currently live in, for both an economic reason (i.e., financial and temporal resource limitations in inclusion of replacement wall rebuilding in the routine surveillance activity components) and a cultural reason (i.e., potential emotional attachment to mud wall at specific households).…”
Section: Discussionmentioning
confidence: 99%